South Caucasus-People's Republic of China Bilateral Free Trade Agreements: Why It Matters - Hasmik Hovhanesian; Heghine Manasyan (Asian Development Bank (ADB), 2014)
Regional integration could be turned into a basic factor for economic growth if combined with a strong economic-development-oriented governmental strategy. The effects of regional integration can be maximized for countries stressing open trade as opposed to creating trade-diverting conditions, which requires drafting different kinds of agreements, particularly free trade agreements (FTAs). The impact of regional integration is significant, especially for small open economies—such as Armenia, Azerbaijan, and Georgia, which together comprise the South Caucasus—entering into an FTA with a large economy like the People's Republic of China (PRC). At the same time, FTAs have mutual economic and geopolitical benefits for all participant countries. Moreover, taking into consideration the interests of countries like Turkey, Iran, and the Russian Federation in the economic and geopolitical potential of this region, the PRC may have to re-think its role in the South Caucasus. This paper assesses the PRC's FTA strategy, the potential for regional integration in the South Caucasus, and the likely impacts of an FTA on the economies of Armenia, Azerbaijan, Georgia, and the PRC by using several specific trade indicators and a partial equilibrium modeling approach (SMART Model).
hdl:11540/1983
Keywords: F13; F15; F17; F43; F53; 330; Free trade agreements; regionalization; South Caucasian countries; PRC; SMART model analysis